Lyme disease in north India: a case for concern. (October 2018) - Tevatia, Pavit; Ahmad, Sohaib; Gupta, Neeti; Shirazi, Nadia
We report Lyme disease in a young man from north India who presented with progressive diminution of vision, severe headache, quadriparesis, seizures, dermatological and pulmonary lesions, lymphadenopathy and a hypocellular bone marrow. This is the first case report of Lyme disease with multi-system involvement from India, confirmed twice by positive serology.